Surgery for locally advanced pancreatic ductal adenocarcinoma - is it only about the vessels? - Heckler, Max; Hackert, Thilo (Journal of gastrointestinal oncology, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is an oligosymptomatic disease, that is usually diagnosed in an advanced tumor stage. Traditionally, only the small subset of patients with tumors that showed no signs of vascular infiltration and distant metastases proceeded to surgery—still the only curative therapeutic modality to date. The remaining majority of patients received palliative chemotherapy or chemoradiation, usually with gemcitabine monotherapy. While gemcitabine monotherapy results in improved survival compared to best supportive care, most patients still succumb to the disease under therapy in a relatively short amount of time. Over the last years and decades, paradigms have shifted in PDAC treatment and potent multidrug chemotherapy protocols, including gemcitabine plus nab-paclitaxel and FOLFIRINOX, result in sufficient downstaging of advanced tumors in many patients. In this context, more and more patients are eligible for exploration and often resection. In this review we discuss the current state of the art in the clinical management and surgical treatment of patients with locally advanced pancreatic cancer, including classifications of locally advanced and borderline disease and surgical strategies for extended resections. An emphasis is put on arterial and venous resections and their outcome. In the end, we discuss current gaps in the literature and propose directions future research endeavors should focus on.